CHALLENGES AT STARTING AN AGRIBUSINESS IN THE HILLY - MOUNTAINOUS REGIONS OF SOUTHWEST SERBIA - Bećirović, Suad; Plojović, Šemsudin; Ujkanović, Enis; Plojović, Senadin (Economics of Agriculture, 2017)
To identify the concrete challenges faced by potential entrepreneurs in agribusiness, a feld research was conducted using unstructured interviews to interview 113 farmers from the municipalities of Novi Pazar, Raška, Sjenica, Tutin, Nova Varoš, Prijepolje, Priboj and Ivanjica. The received answers were classifed into fve groups: infrastructural conditions, access to public services, farm enlargement, market access and availability of funding sources. To solve these problems, the authors propose, among others, investment in infrastructure, change in the taxation of agricultural land, reforming agricultural cooperatives and designing new fnancial instruments according to the needs of farmers and local specifcities. The role of modern cooperatives, where active farmers, land owners and investors will contribute their knowledge and capital, are especially emphasized by the authors.